2012
DOI: 10.1021/ma3010058
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization of Polylactides Immobilized on a Flat Surface: Observation of Single Crystal Arrays of Homochiral and Stereocomplexed Polylactides

Abstract: Formation of single crystal arrays of polylactides (PLA) was found on a flat surface immobilized with poly(D-lactide) (PDLA) having different chain lengths. Monoalkoxydimethylsilyl-terminated PDLAs were synthesized by hydrosilylation of (allyloxy)ethyl-terminated PDLAs and covalently immobilized onto silicon surfaces by a silicone coupling reaction in which the immobilization took place homogeneously through a single Si−O−Si bond. Atomic force microscopy (AMF) of the immobilized surfaces revealed that PDLA cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…4.5 kDa (the first deposit) for surface immobilization of PDLA chains by siloxane bond formation with the surface silanol groups as reported previously. 12,13 Figure 1a shows a typical AFM image of the resultant PDLA-immobilized surface of the first deposit, exhibiting a homogeneous scattering of particulate deposits of PDLA chains. The average thickness of the deposit layer was 3.7 nm with bumpiness less than 0.7 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4.5 kDa (the first deposit) for surface immobilization of PDLA chains by siloxane bond formation with the surface silanol groups as reported previously. 12,13 Figure 1a shows a typical AFM image of the resultant PDLA-immobilized surface of the first deposit, exhibiting a homogeneous scattering of particulate deposits of PDLA chains. The average thickness of the deposit layer was 3.7 nm with bumpiness less than 0.7 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This surface morphology, formed by the aggregation of the terminally anchored PDLA chains, was identical to that reported in our previous study. 13 This surface-modified silicon wafer was then submerged into a CH 2 Cl 2 solution of each of PLLA-PEG (4.6k-5.2k in the block sequence) and PLLA-PEG-PLLA (4.0k-3.2k-4.0k in the block sequence) (the second deposit). The AFM images of the surfaces obtained after the second deposition are shown in Figure 1b spaces ranging from 35 to 60 nm as shown by white bidirectional arrows.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slager and Domb observed the morphology of sc and hetero‐sc formation behavior of PLLA and a peptide l ‐leuprolide, respectively, onto immobilized PDLA on a silicon surface . Our groups reported the direct surface immobilization of PLLA on a silicon surface treated with silyl‐terminated PDLA . As shown in Scheme , two types of silyl‐terminated PDLAs ((MeO) 3 ‐Si‐PDLA and EtO‐Si‐PDLA) having trimethoxysilyl and monoethoxydimethylsilyl terminals were synthesized and immobilized onto silicon surfaces.…”
Section: Specialty Pla Polymers By Controlled Stereocomplex Formationmentioning
confidence: 91%
“…41,42 By the way, Nakajima et al, reported on the deposition of one layer of PLLA-containing diand triblock (conjugated to poly-(ethylene glycol)) onto PDLA chains pre-immobilized on a at silicon surface. 43,44 They evidenced the formation of stereocomplexes on the surface, leading to bumpy surface structures but they focused their work on the deposition of only one copolymer layer, without constructing multilayers. To summarize, stereocomplexation-driven LbL assembled lms including PLA-containing (co)polymers, such as gra copolymers have never been reported so far in literature.…”
Section: Introductionmentioning
confidence: 99%